2018
DOI: 10.1080/23723556.2017.1409863
|View full text |Cite
|
Sign up to set email alerts
|

MHC-I genotype drives early immune selection of oncogenic mutations

Abstract: MHC-I exposes the intracellular contents to immune cells for surveillance of cellular health. Due to high genomic variation, individuals' immune systems differ in their ability to expose and eliminate cancer-causing mutations. These personalized immune blind spots create specific oncogenic mutation predispositions within patients and influence their prevalence across populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“… 8 T-cells against driver mutations have been limited in some settings, presumably due to selection based on HLA genotype. 21 In order to test whether the BRAF V600E mutation could be immunogenic in pediatric tumors, we synthesized peptides encompassing this mutation and used these to detect and expand BRAF V600E -specific T-cells in culture. In a patient with BRAF V600E -mutant LGG and available fresh T-cells, we could demonstrate the presence of V600E-specific T-cell immunity ( online supplementary figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“… 8 T-cells against driver mutations have been limited in some settings, presumably due to selection based on HLA genotype. 21 In order to test whether the BRAF V600E mutation could be immunogenic in pediatric tumors, we synthesized peptides encompassing this mutation and used these to detect and expand BRAF V600E -specific T-cells in culture. In a patient with BRAF V600E -mutant LGG and available fresh T-cells, we could demonstrate the presence of V600E-specific T-cell immunity ( online supplementary figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…After validating the accuracy of the developed classification approach, we aimed to demonstrate its applicability in current molecular biology research. A central controversy in the context of tumor immunology is whether the individual's HLA type influences the mutational landscape of cancers 12–14,37 . With the developed approach, we determined the HLA‐A *02 status of an independent cohort of 73 MSI CRC samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, by determining the repertoire of tumor antigens presented on the cell surface, HLA genotype might also influence the course of cancer progression and the mutational spectrum of arising tumor cell clones during carcinogenetic evolution. Recent studies reported an HLA type‐dependent negative selection of oncogenic mutations, predominantly examining missense mutations 12–14 . In clinical cancer research, investigating HLA type as a predictive marker for the response to immune checkpoint inhibitors has recently gained attention 15 .…”
Section: Introductionmentioning
confidence: 99%
“…231 In tumor cells, autophagy leads to immunogenic cell death by surface exposure of calreticulin (ecto-CRT), secretion of ATP, and release of apoptotic proteins such as HMGB1. 232,233 On the other hand, autophagy can also suppress immune responses. 34 Lysosomal acidification in distinct phases of the pathways that lead to antigen presentation is needed and this need depends heavily on the nature of the antigen.…”
Section: Impact Of Cq On Antitumor Immune Responsesmentioning
confidence: 99%
“…64 MHC-I-driven presentation, which tends to be promoted by CQ, exposes cancer-derived neoantigens to the immune system. 232,233 On the other hand, autophagy can also suppress immune responses. Autophagy, especially under hypoxia, permits activation of transcription factor STAT3, leading to the expression and secretion of cytokines such as IL-10, and a number of other factors with immunosuppressive effects that help cancer cells escape multiple components of the immune system.…”
Section: Impact Of Cq On Antitumor Immune Responsesmentioning
confidence: 99%